Predictors of pulmonary embolism in adult patients following neurosurgery: a Chinese single-center, retrospective study - Gong, Jie; Xie, Baoshu; Wang, Yufang; Zhang, Yanting; Shi, Lei; Yao, Mingli; Li, Jingchao; Ouyang, Bin; Wang, Lingyan; Li, Yan (Neurosurgical review, 2025)
Patients undergoing neurosurgery are at elevated risk for venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE). The incidence and risk factors for PE in neurosurgical patients remain a subject of debate. This study aimed to identify risk factors for PE in this population. We conducted a retrospective case-control study of post-neurosurgical hospitalized patients with PE from January 2017 to March 2023 at the First Affiliated Hospital of Sun Yat-sen University. A control group, matched for age, sex, and entry time (1:3 ratio), consisted of patients without PE. Clinical and biomarker variables were recorded for analysis. Univariate and multivariable logistic regression (MLR) analyses were performed to identify predictive factors for postoperative PE, and diagnostic performance was assessed using receiver operating characteristic (ROC) curve analysis.47 PE patients confirmed by computed tomography pulmonary angiography (CTPA) and 141 matched controls were included. The average annual incidence of PE was 0.4%. MLR identified longer surgical duration (OR 1.404, P < 0.001), higher postoperative D-dimer levels (OR 1.170, P = 0.003), and lower platelet count (OR 0.991, P = 0.040) as independent risk factors for PE. The logistic regression model demonstrated strong diagnostic performance. Prognosis analysis revealed a lower mortality rate in the PE group (10.64%) compared to the non-PE group (20.57%). The clinical prediction model, incorporating surgery duration, postoperative D-dimer levels, and platelet count, effectively identifies patients at high risk for PE following neurosurgery, aiding in prevention strategies.